Growth performance and hematological indices of finisher broilers fed varying levels of Bush Buck (Gongronema latifolium) leaf extract in drinking water - Nwosu, C.I.; Igugo, R.U.; Uwadiegwu, N.C. (Nigerian Journal of Animal Science, 2023)
The study was conducted to investigate the effects and administration of Gongronema latifolium leaf extract (GLLE) on growth, carcass characteristics and hematological indices of broiler finisher birds in drinking water. A total of 270 Marshall Strain commercial finisher broilers were randomly selected and assigned to six experimental treatments namely: T1 (GLLE 0g), T2 (GLLE 5g), T3 (GLLE 10g), T4 (GLLE 15g), T5 (GLLE 20g), and T6 (GLLE 25g). Each treatment was replicated thrice with fifteen (15) birds in each replicate in a completely randomized design (CRD). At the end of 30 days, final body weight and daily weight gain were significantly (P<0.05) higher in birds fed GLLE 15g, followed by birds fed GLLE 10g, then GLLE 5g than those on GLLE 20g & 25g which were not significantly (P >0.05) different from the control. The feed conversion ratio though similar for GLLE 15g and 10g, was better (P <0.05) than GLLE 5g. The carcass weights of GLLE 15g, 10g and 5g were not significantly (P >0.05) different, however, they were significantly (P< 0.05) heavier than those of GLLE 20g, 25g and control. The hematological characteristics of the birds showed significant differences (P < 0.05) in favour of birds on GLLE 15g, GLLE 10g and GLLE 5g than GLLE 20g, 25g and control. It is therefore suggested that administering Gongronema latifolium leaf extract in drinking water improved performance of broiler finishers at 15g, 10g and 5g significantly (P<0.05) than birds fed without the leaf extract.